COVID‐19 restrictions and psychological well‐being of fathers with infants admitted to NICU—An exploratory cross‐sectional study. (26th June 2022) - Adama, Esther Abena; Koliouli, Flora; Provenzi, Livio; Feeley, Nancy; van Teijlingen, Edwin; Ireland, Jillian; Thomson‐Salo, Frances; Khashu, Minesh; ,
Abstract: Aim: To describe the impact of the COVID‐19 restrictions on the caregiving activities and psychological well‐being of fathers with infants admitted to neonatal units. Methods: Cross‐sectional study using adapted COPE‐IS and COPE‐IU tools. Participants' recruitment occurred online via social media and parents' associations. Online survey in English, French and Italian were distributed and promoted via websites and social media platforms of parent's associations. The study was undertaken across 12 countries in Asia, Australia, Africa and Europe. Results: A total of 108 fathers of NICU infants completed the survey. COVID‐19 related restrictions were categorised into 3 types: no restrictions, partial and severe restrictions. Fathers who experienced partial restrictions reported more involvement in caregiving activities but high levels of emotional difficulties and sleeping problems compared to those who experienced full or no restrictions. Conclusion: Given the impact on the psychological well‐being of fathers, restrictions should be avoided as much as possible in the neonatal unit and fathers given free access to their infants if they follow appropriate infection control precautions.